Kicking the "mean" habit: joint prepositioning in debiasing pull-to-center effects (2015)
Behavioral studies of the newsvendor model have revealed systematic underordering for low-cost products and overordering for high-cost products. This systematic deviation from optimal ordering is known as the pull-to-center effect. This chapter proposes a joint newsvendor framework or portfolio that bundles two products of different importance as a strategy to influence pull-to-center behavior. A high-cost, high-importance product is bundled with a low-cost, low-importance product, exposing decision-makers to an inconsistent cost-importance ordering task. In contrast, a low-cost, high-importance product is bundled with a high-cost, low-importance product, exposing decision-makers to a consistent cost-importance ordering task. In both cases, the high-importance product should be more salient relative to the low-importance product, thus inducing larger orders for the high-importance product compared to isolated orders associated with the same product. The framework is tested in a decision-making game portraying an inventory prepositioning task in preparation to emergency response. The prospects for debiasing in these contexts are addressed.